BRCA-related ATM-mediated DNA double-strand break repair and ovarian aging - Turan, Volkan (Hum Reprod Update, 2020)
BACKGROUND: Oocyte aging has significant clinical consequences, and yet no treatment exists to address the age-related decline in oocyte quality. The lack of progress in the treatment of oocyte aging is due to the fact that the underlying molecular mechanisms are not sufficiently understood. BRCA1 and 2 are involved in homologous DNA recombination and play essential roles in ataxia telangiectasia mutated (ATM)-mediated DNA double-strand break (DSB) repair. A growing body of laboratory, translational and clinical evidence has emerged within the past decade indicating a role for BRCA function and ATM-mediated DNA DSB repair in ovarian aging. OBJECTIVE AND RATIONALE: Although there are several competing or complementary theories, given the growing evidence tying BRCA function and ATM-mediated DNA DSB repair mechanisms in general to ovarian aging, we performed this review encompassing basic, translational and clinical work to assess the current state of knowledge on the topic. A clear understanding of the mechanisms underlying oocyte aging may result in targeted treatments to preserve ovarian reserve and improve oocyte quality. SEARCH METHODS: We searched for published articles in the PubMed database containing key words, BRCA, BRCA1, BRCA2, Mutations, Fertility, Ovarian Reserve, Infertility, Mechanisms of Ovarian Aging, Oocyte or Oocyte DNA Repair, in the English-language literature until May 2019. We did not include abstracts or conference proceedings, with the exception of our own. OUTCOMES: Laboratory studies provided robust and reproducible evidence that BRCA1 function and ATM-mediated DNA DSB repair, in general, weakens with age in oocytes of multiple species including human. In both women with BRCA mutations and BRCA-mutant mice, primordial follicle numbers are reduced and there is accelerated accumulation of DNA DSBs in oocytes. In general, women with BRCA1 mutations have lower ovarian reserves and experience earlier menopause. Laboratory evidence also supports critical role for BRCA1 and other ATM-mediated DNA DSB repair pathway members in meiotic function. When laboratory, translational and clinical evidence is considered together, BRCA-related ATM-mediated DNA DSB repair function emerges as a likely regulator of ovarian aging. Moreover, DNA damage and repair appear to be key features in chemotherapy-induced ovarian aging. WIDER IMPLICATIONS: The existing data suggest that the BRCA-related ATM-mediated DNA repair pathway is a strong candidate to be a regulator of oocyte aging, and the age-related decline of this pathway likely impairs oocyte health. This knowledge may create an opportunity to develop targeted treatments to reverse or prevent physiological or chemotherapy-induced oocyte aging. On the immediate practical side, women with BRCA or similar mutations may need to be specially counselled for fertility preservation.